Pride and joy : a novel - Onomé, Louisa (Atria Books, 2024)
"Joy Okafor is overwhelmed. Recently divorced, a life coach whose phone won't stop ringing, and ever the dutiful Nigerian daughter, Joy has planned every aspect of her mother's seventieth birthday weekend on her own. As the Okafors slowly begin to arrive, Mama Mary goes to take a nap. But when the grandkids go to wake her, they find that she isn't sleeping after all. Refusing to believe that her sister is gone-gone, Auntie Nancy declares that she has had a premonition that Mama Mary will rise again like Jesus Christ on Easter Sunday. Desperate to believe that they're about to witness a miracle, the family overhauls their birthday plans to welcome the Nigerian Canadian community, effectively spreading the word that Mama Mary is coming back. But skeptical Joy is struggling with the loss of her mother and not allowing herself to mourn just yet while going through the motions of planning a funeral that her aunt refuses to allow"--